2006
DOI: 10.1128/aem.72.4.2849-2855.2006
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic Vibrio cholerae in the Aquatic Environment of Mathbaria, Bangladesh

Abstract: Toxigenic Vibrio cholerae, rarely isolated from the aquatic environment between cholera epidemics, can be detected in what is now understood to be a dormant stage, i.e., viable but nonculturable when standard bacteriological methods are used. In the research reported here, biofilms have proved to be a source of culturable V. cholerae, even in nonepidemic periods. Biweekly environmental surveillance for V. cholerae was carried out in Mathbaria, an area of cholera endemicity adjacent to the Bay of Bengal, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
149
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 46 publications
14
149
0
Order By: Relevance
“…V. cholerae serogroups O1 and O139 have been shown to survive year round, mostly in a nonculturable state, within clusters of biofilm in the ecosystem adjacent to the coast of the Bay of Bengal, accounting for the endemic cholera in that geographic region [7]. Biofilm-like, multicellular clumps of V. cholerae are found in human stools [8], and a recent epidemiological and ecological study offered firm evidence that bodies of water serving as drinking water sources harbored biofilm-bound, nonculturable V. cholerae O1 cells between epidemics occurring in the coastal villages of the Bay of Bengal seasonally [9].…”
Section: Formation Of Biofilm In Aquatic Environmentsmentioning
confidence: 99%
“…V. cholerae serogroups O1 and O139 have been shown to survive year round, mostly in a nonculturable state, within clusters of biofilm in the ecosystem adjacent to the coast of the Bay of Bengal, accounting for the endemic cholera in that geographic region [7]. Biofilm-like, multicellular clumps of V. cholerae are found in human stools [8], and a recent epidemiological and ecological study offered firm evidence that bodies of water serving as drinking water sources harbored biofilm-bound, nonculturable V. cholerae O1 cells between epidemics occurring in the coastal villages of the Bay of Bengal seasonally [9].…”
Section: Formation Of Biofilm In Aquatic Environmentsmentioning
confidence: 99%
“…In response to environmental stress in aquatic environments, such as low concentrations of nutrients and low temperatures, V. cholerae O1 and non-O1 adopt a viable state that enables them to carry out metabolic functions and form colonies without being culturable (Huq et al 1990, Colwell et al 1985, Brayton et al 1986, Colwell et al 1992. The above information suggest that the ecology of Vibrio cholerae is mostly correlated with water and plankton samples of aquatic environment and the non culturable cells play a significant role in the seasonal epidemics of cholera (Alam et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, cholera epidemics occur twice every year, the highest peak during post monsoon (September -January) and second smaller peak during pre monsoon (MarchMay). During inter-epidemic period V. cholerae cannot be cultured from the surface water, whereas in epidemic season it can be isolated from the patients' body as well as from surface water (Alam et al 2006). When V. cholerae is not causing havoc in the human intestine, it may be found in diverse aquatic environments such as estuaries, rivers, ponds etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the same laboratory and others revealed that El Tor variant strains of V. cholerae have replaced seventh pandemic El Tor prototype strains in most of the cholera-endemic areas in Asia and Africa Safa et al, 2010 . Recent Haitian V. cholerae strains, pathogens of the cholera outbreak after the 2010 Great Earthquake, contained a unique mutation at the 58th nucleotide of the ctxB gene resulting in a change at the 20th position with an asparagine instead of histidine in the signal peptide region of cholera toxin B. CRCOUI showed that Haitian ctxB first appeared in Kolkata and also in Delhi Many investigators have suggested the existence of VBNC V. cholerae O1 and O139 in environmental water sources in cholera-endemic areas Roszak and Colwell, 1987;Alam et al, 2006 . Even between epidemic seasons, VBNC V. cholerae O1 is present as a biofilm Faruque et al, 2006;Alam et al, 2007 .…”
Section: El Tor Variant V Choleramentioning
confidence: 99%